2022
DOI: 10.1002/cssc.202200186
|View full text |Cite
|
Sign up to set email alerts
|

Solvent‐Free Hydrogenation of 5‐Hydroxymethylfurfural and Furfural to Furanyl Alcohols and their Self‐Condensation Polymers

Abstract: 2,5-Bis(hydroxymethyl)furan (BHMF) as well as furfuryl alcohol (FFA) are considered as highly valuable biomass-derived alcohols resembling aromatic monomers in polymer synthesis. Herein, a series of cobaltic nitrogen-doped carbon (CoÀ NC) catalysts calcinated at different temperatures were synthesized and tested for the solvent-free hydrogenation of 5hydroxymethylfurfural (HMF) to prepare BHMF. It was found that the CoÀ NC catalyst calcinated at 600 °C (CoÀ NC-600) exhibited a superior catalytic activity in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…Schematic representation of BHMF conversion to a hyper-cross-linked polymer (HCP). Reproduced with permission from ref . Copyright 2022 Wiley-VCH GmbH.…”
Section: Synthesis Of Other Bhmf-based Polymersmentioning
confidence: 99%
See 1 more Smart Citation
“…Schematic representation of BHMF conversion to a hyper-cross-linked polymer (HCP). Reproduced with permission from ref . Copyright 2022 Wiley-VCH GmbH.…”
Section: Synthesis Of Other Bhmf-based Polymersmentioning
confidence: 99%
“…Recently, Wang et al used a cobaltic nitrogen-doped carbon catalyst for the production of BHMF from HMF in high conversion and yield, 99.3% and 91.5%, respectively. 69 Subsequently, BHMF was used for the production of a porous hyper-cross-linked polymer (HCP) (Figure 7), meant for CO 2 /H 2 storage. This was achieved via a Friedel−Crafts alkylation reaction using ferric chloride as the catalyst and 1,2dichloroethane as the solvent.…”
Section: ■ Synthesis Of Other Bhmf-based Polymersmentioning
confidence: 99%
“…This implied that the calcination temperature has an important impact on the formation of defects over CoNC as confirmed by previous works. 43,44…”
Section: Resultsmentioning
confidence: 99%
“…For example, an 89% yield of MFA was obtained after increasing the temperature and H 2 pressure to 100 °C and 30 bar, respectively. Wang et al (Wang et al 2022c ) reported the solvent-free synthesis of FDM from HMF over cobaltic nitrogen-doped carbon (Co–NC) catalysts, and a desirable FDM yield of 91.5% was afforded at 90 °C in the presence of 50 bar H 2 . The doped graphitic N might facilitate the polarization of H 2 to form H + and H – , which promoted the hydrogenation of HMF.…”
Section: Synthesis Of Fdm From Hmfmentioning
confidence: 99%